Experimental simulation of biodegradation in rivers. Oxygen, organic matter and biomass concentration changes - Apoteker, A.; Thevenot, D.R. (Water Research, 1983)
Dissolved oxygen (DO) and biochemical oxygen demand (BOD) concentration changes after an organic matter discharge into a river have been studied in the absence of oxygen transfer. According to these laboratory experiments, biodegradation of various organic compounds (glucose, glutamic acid, starch, ovalbumin and ethanol) in Seine river samples incubated at 15-30°C follow a biphasic behaviour. During a lag-phase of 10-20 h, DO decreases linearly (0.12 ppm h-1 at 20°C), whereas BOD is constant. During a subsequent aerobic exponential phase, DO and BOD uptake are proportional and increase exponentially with time (0.13 h-1 at 20°C). Using cell ATP as biomass indicator, the latter phase was shown to correspond to a cell division step. A kinetic model was developed for stimulating DO and BOD concentration changes after a waste water discharge at temperatures ranging between 15 and 30°C.